Evaluating the safety of phytosterols removed perilla seed oil-based lipid emulsion. (2nd October 2016) - Yang, Zhenhua; Ren, Tianyang; Lu, De; Guo, Haiyan; Li, Wanqiu; Huang, Chenglong; He, Haibing; Liu, Dongchun; Tang, Xing
ABSTRACT: Objectives : The aim of this study was to ascertain the potential toxicity of perilla seed oil-based lipid emulsion (POLE) caused by phytosterols and confirm the efficacy of the technique for removing phytosterols from perilla seed oil, and evaluate the safety of a low phytosterol POLE in a long-term tolerance study in dogs. Methods : A comparison between a soybean oil lipid emulsion (Intralipid group A) and POLE with high (group B) versus low (group C) levels of phytosterols was made with regard to their effects on the general condition, hematological and biochemical parameters, urinalysis and histopathological changes in nine dogs receiving daily infusions for four weeks at dosage levels of 6, 6, 9 g fat /kg. Results : Dogs in group A and group C remained in good condition and gained weight during the infusion period and no diarrhea or gastrointestinal bleeding occurred. Only a moderate degree of anemia was observed, the biochemical parameters changed only slightly and returned to normal after treatment had ceased. However, the dogs in group B exhibited significant symptoms of 'fat overload syndrome'. Vomiting, diarrhoea and blood in the faeces were observed. Moreover, triglyceridemia, cholesteremia, and dark urine as well as microscopic signs of liver and gastrointestinal tract damage and generalized jaundice were clearly seen. Conclusions : Phytosterols promote 'fat overload syndrome' in long-term tolerance studies of POLE in dogs by producing cholestatic liver injury and interfering with fat metabolism. And the toxicity of POLE was reduced by removing phytosterols.